Effect of Supply Chain Management Practices on Contract Dispute Resolution in Nigeria’s Public Sector - Abubakar, Sadeeq Ahmad; Okoli, Theresa Omang (Kashere Journal of Politics and International Relations, 2024)
This study investigates the effect of supply chain management practices on contract dispute resolution within Nigeria’s public sector. Utilizing a mixed-methods approach, the research integrates quantitative data from surveys from procurement professionals and public sector managers. The study aims to assess how various procurement practices, such as supplier relationship management, procurement planning, and contract administration, influence the frequency and resolution of contract disputes. Findings indicate that effective supply chain management practices significantly contribute to reducing contract disputes by improving transparency, communication, and compliance in procurement processes. Quantitative analysis revealed a strong correlation between robust procurement practices and a reduction in dispute occurrences, supported by a chi-square test demonstrating a significant relationship (χ² = 12.1, p < 0.05). Conversely, the impact of court judgments on dispute resolution was found to be less significant, with enforcement challenges and procedural delays mitigating their effectiveness. The study underscores the importance of proactive procurement strategies in minimizing disputes and suggests that while judicial interventions are necessary, their effectiveness can be significantly enhanced through improved enforcement mechanisms. The research contributes to the understanding of how procurement management can be optimized to address and resolve disputes more effectively in the Nigerian public sector, offering recommendations for policy improvements and future research directions.